Evaluasi User Interface pada BNI Mobile Banking Menggunakan Metode Evaluasi Heuristik - Maysa Putra, I Putu Gede; Raharja, Made Agung (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
With the advancement of Information Technology today, fields such as banking compete to get more users by improving services to be more practical. One of the banks that has launched an application that is useful to facilitate customers in conducting transactions is Bank Negara Indonesia (BNI). BNI launched the BNI Mobile Banking application with several features in it. This study will try to evaluate the design of this application interface with User Usability using the Heuristic Evaluation method which is based on 10 aspects. User Usability is used to determine an application can be categorized, to determine an application deserves to be called user-friendly and to simplify the application development process. In addition, data was collected through questionnaires whose values ??were obtained from 33 respondents. In the process of testing the validity we use the Pearson correlation and in the process of reliability we use the Cronbach's Alpha method. The final result of the study shows that the BNI Mobile Banking application as a whole has met the Usability Test component with an average value of 3, which means that this application already has a Usability aspect value which can be said to be normal